"Novel Dextrin‐Cysteine Schiff Base: A Highly Efficient Sensor for Mercury Ions in Aqueous Environment". Issue 6 (13th February 2020) - Mondal, Barun; Banerjee, Shankha; Ray, Jagabandhu; Jana, Subinoy; Senapati, Sanjib; Tripathy, Tridib
Abstract: We report a highly sensitive electrochemical and fluorescence sensor for the detection of toxic environmental pollutant Hg 2+ ions by using a novel dextrin‐cysteine‐Schiff base (DCS). The sensor is developed by the periodate oxidation of dextrin followed by Schiff base formation with an amino acid, cysteine. The new characterized DCS is used as an efficient and selective sensor for the detection of Hg 2+ ions in aqueous solution both by electrochemical and fluorescence quenching process. The detection limit (LOD) by the electrochemical method is 0.74 nM which is much lower than that by the fluorometric detection, where LOD value is found to be 40.93 μM. The Schiff base/glassy carbon electrode (DCS/GCE) shows an excellent selectivity towards Hg 2+ ions compare to other environmentally relevant ions where almost nil current response is observed. The DCS/GCE also exhibits remarkable sensing of Hg 2+ in real water samples such as river and tap water. The electrochemical sensing of Hg 2+ by DCS is found to be superior to that of fluorescence sensing. Abstract : Herein, we report a novel Dextrin‐Cysteine‐Schiff base sensor for the detection of Hg 2+ ions by electrochemical and fluorescence sensing studies for the first time. The present Schiff base sensor is more efficient by electrochemical detection of Hg 2+ ions (LOD = 0.74 nM) than fluorometric sensing for the same (LOD = 40.93 μM) in water medium.